O discurso de intimidade: a paixão semiótica - amizade - nas comunidades do Orkut - Woodson Fiorini de Carvalho (2012)
This study is an analysis of the Orkut network and its communities found in Belo Horizonte/MG.It aims at investigating, from the analysis of the lexico-semantic configuration of the passionFriendship and the generativist course of meaning in this Social Network, which syntactic andsemantic structures (of the social networking system and these digital communities) will negotiatethe friendship content. The manifestation of this friendship on Orkut is produced, essentially, inwritten form, adorned by pictures and graphic elements that create the message in a multimodal andsyncretic text. On Orkut, this friendship is a representation of what we assume to be this passion,which is formed behind an ideology and accommodates the system social network applications.The ideology of this system results from applications that articulate the relations and meaningsproduced within it in a pre-established and pre-molded fashion. The content, then, undergoes acanonical recipe of how to make friendships being regulated by the conformation of themechanism of this social network, in a euphoric certainty that these friendships will happeninexorably through this system.